Bogo: The Winged Boat Of The Sea Bajau in Sabah - Ismail Ali; Wong Kon Ling (2008)
The Sea Bajau or Pala'u is one of the Bajau ethnic groups residing on the east coast of Sabah. The community practises a sea nomad's lifestyle and is famous for its lepa-lepa boat in which they dwell. To preserve its heritage and culture, Sabah's Ministry of Tourism, Culture and Environment has listed the ' Lepa-Lepa Festival' as one of the events on the Sabah tourism calendar. Apart from lepa-lepa, the Sea Bajau community also has another type of uniquely designed boat called boo'gok-boo'-gok. It is a winged boat used for fishing. However, scholars who study this community seldom mention it. This article highlights the boo'gok-boo'gok as part of the cultural heritage of this community.